ARCIMBOLDO_LITE: single‐workstation implementation and use. (1st September 2015) - Sammito, Massimo; Millán, Claudia; Frieske, Dawid; Rodríguez‐Freire, Eloy; Borges, Rafael J.; Usón, Isabel
<x xml:space="preserve">Abstract</x> ARCIMBOLDO solves the phase problem at resolutions of around 2 Å or better through massive combination of small fragments and density modification. For complex structures, this imposes a need for a powerful grid where calculations can be distributed, but for structures with up to 200 amino acids in the asymmetric unit a single workstation may suffice. The use and performance of the single‐workstation implementation, ARCIMBOLDO_LITE, on a pool of test structures with 40–120 amino acids and resolutions between 0.54 and 2.2 Å is described. Inbuilt polyalanine helices and iron cofactors are used as search fragments. ARCIMBOLDO_BORGES can also run on a single workstation to solve structures in this test set using precomputed libraries of local folds. The results of this study have been incorporated into an automated, resolution‐ and hardware‐dependent parameterization. ARCIMBOLDO has been thoroughly rewritten and three binaries are now available: ARCIMBOLDO_LITE, ARCIMBOLDO_SHREDDER and ARCIMBOLDO_BORGES. The programs and libraries can be downloaded from http://chango.ibmb.csic.es/ARCIMBOLDO_LITE.